Female transactional sex workers’ experiences and health-seeking behaviour in low-middle income countries: a scoping review - Wulifan, Joseph Kwame (BMC public health, 2024)
For a variety of reasons related to biology, behaviour, and environment, a subset of a population known as female sex workers (FSWs) or female transactional sex workers is at increased risk of health, depression, social stigma and access to timely and quality healthcare when needed. In low- and middle-income countries (LMICs), there was lack of understanding regarding the experiences and healthcare utilisation and behaviours, the health burden among them, their experiences, and how they access health care. Using Anderson's behavioural model of health service utilisation as a framework, this review aimed to explore the experiences of, and healthcare seeking behaviours of female sex workers in low-and middle-income countries. Six relevant databases such as PubMed, Embase, Global Health, Scopus, Web of Science, and Google Scholar were searched for peer-reviewed research articles published between January 1990 and December 2023 that discussed female transactional sex work in low- and middle-income countries. Subject terms such as: low-and middle- incomes, sex workers (female and male), sexually transmitted infections (STIs) in the sex work industry, prostitution, commercial sex, and health-seeking behaviour were used for the databases search. Out of 6,135 articles that were retrieved for the study, 26 met the inclusion criteria. Of the total number of studies, four were reviews, eight were quantitative studies, six were qualitative studies, and two utilised mixed methods. Results from a thematic analysis of studies that combined quantitative and qualitative methods yielded six overarching themes.The study found that women engaged in sex work for different reasons - to fend for themselves (i.e., livelihood), self-employment and others do it for pleasure. However, force sex or unprotected which can lead to sexually transmitted infections, sexual abuse, job insecurity, were critical risks factors in engaging in sex work. These factors make them vulnerable to predators and health risks. It was found that sex workers were aware of the importance of seeking healthcare, and do make the efforts, however, crucial factors such as difficulty accessing healthcare and maltreatment by healthcare providers and social stigma disincentivises FSW health-seeking behaviours. Sexual workers reported discomfort disclosing their occupations because of the stigma and discrimination which further affects their regular health examinations and obtaining medically approved condoms from healthcare facilities. Complex challenges rooted in economic vulnerability, social marginalisation, and limited access to healthcare afflict female sex workers in LMICs. The maltreatment and stigma can potentially affect LMICs from achieving using health facility care, with potential implications on achieving the universal health coverage goals. Comprehensive, rights-based strategies that address structural injustices and empower these women to live healthier, more secure lives are necessary to address their special needs.